Wild fauna in Oman: Current situation and perspectives, with particular interest to turtles and ungulates - Massimo Giangaspero; Salah Al Mahdhori; Sultan Al Bulushi; Ali Salim Bait Said; Metab Khalaf Salim Al Ghafri (Open Veterinary Journal)
In order to achieve optimal health for humans, animals, and our environment, the "One Health" approach proactively engages various disciplines, including environmental health sciences, veterinary medicine, and human medicine. Therefore, wildlife conservation assumes a relevant role in this context. The Sultanate of Oman is a country with an immense biodiversity. In recent decades, authorities have actively protected wildlife and the natural environment. In 1994, the Arabian Oryx Sanctuary was created under the patronage of the Royal Diwan. The Environment Authority was recently established, and the plan "Vision 2040" was conceived with the ambitious goal of Oman becoming one of the top 20 countries for wildlife protection. Two species in particular show the amplitude of the efforts necessary to preserve this natural heritage and their survival: the oryx of Arabia and the green turtle. The oryx is not only a national symbol but, from extinction in nature, its return is also a success for the Omani sanctuary. The green turtles elected the Omani coasts as the second reproduction site in the world. Therefore, the delicate equilibrium of wild fauna in Oman requires to be studied and supported. [Open Vet J 2025; 15(1.000): 35-53]